Proposal for a tiered regulatory framework for the aquatic risk assessment of pesticides in Brazil - Santos, Gustavo Souza (2024)
Publisher Copyright: © 2024 The Authors. Integrated Environmental Assessment and Management published by Wiley Periodicals LLC on behalf of Society of Environmental Toxicology & Chemistry (SETAC).